2021
DOI: 10.3390/antibiotics10020110
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of COVID-19 on Antimicrobial Stewardship Activities/Programs in the United Kingdom

Abstract: Since first identified in late 2019, the acute respiratory syndrome coronavirus (SARS-CoV2) and the resulting coronavirus disease (COVID-19) pandemic has overwhelmed healthcare systems worldwide, often diverting key resources in a bid to meet unprecedented challenges. To measure its impact on national antimicrobial stewardship (AMS) activities, a questionnaire was designed and disseminated to antimicrobialstewardship leads in the United Kingdom (UK). Most respondents reported a reduction in AMS activity with 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 27 publications
0
99
1
3
Order By: Relevance
“…3 , 19 , 20 The current COVID-19 (Coronavirus disease of 2019) pandemic context has changed the priorities of the medical activity by influencing antibiotic use with unknown consequences in the long run. 21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 , 19 , 20 The current COVID-19 (Coronavirus disease of 2019) pandemic context has changed the priorities of the medical activity by influencing antibiotic use with unknown consequences in the long run. 21 …”
Section: Introductionmentioning
confidence: 99%
“…3,19,20 The current COVID-19 (Coronavirus disease of 2019) pandemic context has changed the priorities of the medical activity by influencing antibiotic use with unknown consequences in the long run. 21 This study aimed to evaluate the evolution of the main antimicrobial resistance issues, as part of the stewardship antibiotic program in an infectious diseases hospital which is representative for the south-east region of Romania.…”
Section: Introductionmentioning
confidence: 99%
“…A summary with the key findings can be seen in Table 1. Literature reports great concern among healthcare workers regarding excessive prescription rates, the use of broad-spectrum antibiotics, prolonged antibiotic treatments without clinical justification, and inappropriate prescribing of antibiotics to patients infected with COVID-19 [7][8][9][10][11][12]. For example, in the United Kingdom, Zhu et al found that clinicians prescribed more broad-spectrum antibiotics due to the inability to assess patients face-to-face [13].…”
Section: Resultsmentioning
confidence: 99%
“…The COVID-19 challenges combine with ongoing lack of knowledge about proper antibiotic use among health professionals, including a "just-in-case" prescription [8,17,18], and the use of experimental antibiotic treatments due to the absence of specific treatments against COVID-19 that might increase the use of non-essential antibiotics [9,11,17]. The "just-in-case" prescription was related to the decrease in education and training activities included in the AMS programmes, negatively affected by the pandemic [8]. Added to this is clinical uncertainty about COVID-19, leading clinicians to prescribe antibiotics without medical indication, based on the perception that the potential benefit was greater than the risk [16,17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation